THE EFFECT OF WORKING CAPITAL EFFICIENCY ON BPRS PROFITABILITY IN ACEH - Syawal harianto; Haris Al Amin; Abdul Halim (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
The purpose of this study was to examine the effect of the use of working capital on profitability (ROA) at Islamic People's Financing Banks (BPRS) in Aceh by using secondary data in the form of panel data. The results of the analysis show that simultaneously, cash turnover, accounts receivable turnover, and working capital turnover have a significant effect on ROA. Partially, cash turnover and accounts receivable turnover do not have a significant negative effect on ROA, while working capital turnover has a significant positive effect on ROA. The effect of the three variables on ROA is 44.78%, while the remaining 55.22% is explained by other factors not included in this study. All classical assumptions have been fulfilled and the analytical method used is panel data regression with the Common Effects model.